Analysis of Regional Economic Growth Potential Based on Shift Share Approach in Trenggalek District - Riko Setya Wijaya; Cholid Fadil (Future Science, 2020)
Economic growth is one of the benchmarks that can be used to increase the development of a region from various economic sectors, which indirectly describes the level of economic change, economic growth means the development of activities in the economy that causes goods and services to be produced to increase and the prosperity of society to increase. The purpose of this study was to determine the potential for economic growth in East Java Province, especially in Trenggalek Regency, to be used as a driver for economic growth and regional development in East Java Province. The analysis of this research is descriptive quantitative research. The data used in this study are secondary data and time series. Using the Shift Share analysis tool. Based on the average results of the Shift Share (Regional Potential) analysis which encouraged the growth of the Provincial Gross Regional Domestic Product in 2017-2018 in Trenggalek Regency as many as 13 sectors, while in 2018-2019 there were 12 sectors, while the sectors that grew relatively fast (Proportional Shift ) at the provincial level in 2017-2018 there were 9 sectors in Trenggalek Regency, while in 2018-2019 there were 10 sectors, and there were 14 Sectors that had a Locational advantage (Differential Shift) in 2017-2018 in Trenggalek Regency, while in 2018-2019 as many as 9 sectors.